The Da Vinci code - Brown, Dan (Corgi Books, 2006)
The elderly curator of the Louvre has been brutally murdered inside the museum. Alongside the body, police have found a series of baffling codes. As Profesor Robert Langdon and a French cryptologist, Sophie Neveu, begin to sort through the riddles, they are stunned to find a trail that leads to the works of Leonardo Da Vinci.